Etnography of daily routine, an anthropological look on Italy which changes - Naputano, Marcelo [UNESP]; Justo, Jose Sterza [UNESP] (Univ Federal Fluminense, Inst Ciencias Sociedade & Desenvolvimento Regional, 2019)
This paper consists in a contextualized review of Marco Aime's bibliographic production, author of the book Etnography of daily routine, an anthropological look on Italy which changes published in Italy, in 2014, with a preface written by Jean-Loup Amselle. Marco Aime is currently professor of cultural anthropology at University of Genova, known as one of the most important Italian anthropologists of our time for the extension and originality of his work. It focuses on the attempt to look at current social and political issues from the point of view of a social anthropology engaged and committed to various social movements. In Ethnography of daily routine we find the analysis of some current Italian issues divided in two categories: political issues related to participant democracy the first, and issues about the construction of the imaginary the second. Aime confirms that politics and anthropology are closely related.
Keywords: Anthropology; ethnography; daily